Trust management X : 10th IFIP WG 11.11 International Conference, IFIPTM 2016, Darmstadt, Germany, July 18-22, 2016, Proceedings /: 10th IFIP WG 11.11 International Conference, IFIPTM 2016, Darmstadt, Germany, July 18-22, 2016, Proceedings. (2016) - Unknown
No abstract available